Daily acoustic presence of Antarctic blue whales within a 10 km radius of mooring AWI209-06, recorder AU0086, based on passive acoustic recordings in the Weddell Sea from December 2010 to January 2013 - Thomisch, Karolin; El-Gabbas, Ahmed; Spiesecke, Stefanie; Boebel, Olaf (In: Thomisch, K et al. (2023): Daily acoustic presence of Antarctic blue whales (Balaenoptera musculus intermedia) within a 10 km radius of recording sites in the Weddell Sea, based on passive acoustic monitoring data from 2008 to 2013 [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.959969, 2023)
Acoustic presence data on Antarctic blue whales (Balaenoptera musculus intermedia) were obtained from passive acoustic monitoring (PAM) data collected at 66°36.70' S and 27°07.31' W, mooring AWI209-06, recorder AU0086, between December 2010 and January 2013. The passive acoustic recorder was of type AURAL (Autonomous Underwater Recorder for Acoustic Listening (AURAL; Model 2, Multi-Électronique) and attached to oceanographic deep-sea mooring AWI209-06 of the Hybrid Antarctic Float Observation System (HAFOS). It was deployed from December 2010 to January 2013, moored at a depth of 207 m and scheduled to record on a duty cycle of 4.5 min per 3 hours at a sample rate of 32.768 Hz. After recovery, the passive acoustic data were prepared for further analysis following the Standard Operating Procedures (SOP) for PAM data collected by the Ocean Acoustics Group of AWI according to Thomisch et al. (2023a, regarding definitions and terminology) and Thomisch et al. (2023b, with regard to data preparation procedures). Daily acoustic presence of Antarctic blue whales was assessed based on automated detections of Z-call vocalizations by spectrogram cross-correlation using a pre-defined spectrogram template in a frequency band from 17.5 to 29 Hz. Received levels were obtained for each detected Z-call, as sound pressure level SPLrms [dB re: 1μPa] within the 25–29 Hz band of each detected Z-call event, for details on automated detection please refer to Thomisch et al. 2016. To avoid a spatial mismatch between the actual position of calling animals and the recorders, ABW detections were filtered to only keep detections that originated from within a ~10 km radius from the recorders. Assuming a source level of 189 dB re: 1μPa over 25–29 Hz and a spherical transmission loss TL[dB] = 20log₁₀(r), approximate distances between vocalizing Antarctic blue whales and the respective recording site locations were estimated for each detected Z-call. Daily acoustic presences were estimated as days with at least one detection event within a ~10 km radius of the respective recording sites; i.e., Z-calls with calculated received levels of ≥109 dB, considering a nominal TL of 80 dB. Data presented in this publication series were used together in presence-only species distribution models (SDMs) to predict the year-round habitat suitability of Antarctic blue whales in the Weddell Sea (El-Gabbas et al. submitted). Data contain information on the detection time and the estimated received level SPLrms [dB re: 1μPa] for each Antarctic blue whale vocalization within a ~10 km radius of recorder AU0086, mooring site AWI209-06.
Keywords: acoustic occurrence; Antarctic blue whales; automated detection; passive acoustic monitoring (PAM); received levels; Southern Ocean; species distribution models; vocalizations; Weddell Sea